2013
DOI: 10.1111/jch.12122
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Uncontrolled Hypertension in the Stroke Belt

Abstract: Inadequate control of high systolic blood pressure in older adults has been largely attributable to poor control of overall hypertension (HTN). The Seventh Report of the Joint National Committee on Prevention, Detection, Evaluation, and Treatment of High Blood Pressure (JNC 7) guidelines emphasize the importance of controlling isolated systolic HTN in older adults. The study examined demographics, self‐reported health information, and clinical measures as predictors of uncontrolled HTN among individuals taking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…This is particularly concerning in light of a higher prevalence of certain stroke risk factors in this population, namely uncontrolled hypertension. 31 Black race has also been shown to be associated with longer prehospital delays 32 and higher mortality rates, 33 making this an especially vulnerable group.…”
Section: Discussionmentioning
confidence: 98%
“…This is particularly concerning in light of a higher prevalence of certain stroke risk factors in this population, namely uncontrolled hypertension. 31 Black race has also been shown to be associated with longer prehospital delays 32 and higher mortality rates, 33 making this an especially vulnerable group.…”
Section: Discussionmentioning
confidence: 98%
“…Similar findings have been reported in other studies that investigated the predictors of uncontrolled AH and the relationship between SBP and DBP control and the risk of coronary heart disease. 22 The hemodynamic patterns of age-related changes in BP have been explored by Franklin and colleagues. 23 They attributed the continuous rise in SBP throughout life, coupled with an early rise and late fall (after the age of 50) in DBP, to large artery stiffness.…”
Section: Predictors Of Uncontrolled Sbp and Dbp Of Either Sexmentioning
confidence: 99%
“…This is in agreement with most of the existing evidence. 22 The Combination Pill of Losartan Potassium and Hydrochlorothiazide for Improvement of Medication Compliance Trial (COMFORT) 29 demonstrated that patients with a relatively low adherence rate (<90%) showed significantly higher systolic and diastolic BP compared with those with a perfect adherence rate (100%) over a 6-month treatment period.…”
Section: Predictors Of Uncontrolled Sbp and Dbp Of Either Sexmentioning
confidence: 99%
“…Estimates from the National Health Interview Survey in 2007 found that Native Hawaiians and Pacific Islanders had the second highest rates of any ethnic group in the United States at 29% [2-5]. Despite evidence that appropriate pharmacological treatment reduces morbidity and mortality across all populations [6-8], racial and ethnic minorities, including African Americans and Native Hawaiian and Pacific Islanders, often underutilize antihypertensive medications [9-11]. …”
Section: Introductionmentioning
confidence: 99%